Recurrence Risk after First Symptomatic Distal versus Proximal Deep Vein Thrombosis According to Baseline Risk Factors - Valerio, Luca; Ambaglio, Chiara; Barone, Marisa; Ciola, Mariella; Konstantinides, Stavros V.; Mahmoudpour, Seyed H.; Picchi, Chiara; Pieresca, Carla; Trinchero, Alice; Barco, Stefano (TH Open, 2019)
Background It remains unclear whether the distal location of deep vein thrombosis (DVT) is independently associated with a lower risk of recurrence in all patients, or represents a marker of the presence and severity of provoking factors for venous thromboembolism (VTE).Methods We investigated the impact of distal (vs. proximal) DVT location on the risk of developing symptomatic, objectively confirmed recurrent VTE in 831 patients with a first acute symptomatic DVT not associated with pulmonary embolism (PE), who were stratified by the presence of transient or persistent risk factors at baseline. The primary outcome was symptomatic, objectively diagnosed recurrent VTE, including proximal DVT and PE.Results A total of 205 (24.7%) patients presented with a transient risk factor, 189 (22.7%) with a minor persistent risk factor, 202 (24.3%) with unprovoked DVT, and 235 (28.3%) with cancer-associated DVT. One-hundred twenty-five patients (15.0%) experienced recurrent DVT or PE. The largest relative difference between patients with distal (vs. proximal) DVT was observed in the absence of identifiable risk factors (adjusted hazard ratio [aHR]: 0.11; 95% CI [confidence interval]: 0.03–0.45). In patients with cancer, distal and proximal DVT had a comparable risk of recurrence (aHR: 0.70; 95% CI: 0.28–1.78]).Conclusions The distal (vs. proximal) location of first acute symptomatic DVT represented, in the absence of any identifiable transient or persistent risk factors, a favorable prognostic factor for recurrence. In contrast, the prognostic impact of DVT location was weaker if persistent provoking risk factors for VTE were present, notably cancer.
Keywords: venous thromboembolism; pulmonary embolism; prognosis; epidemiology